Loving life eaudiobook In a world of broken relationships. - Miller DVM, DACVO, Paul E. (christianaudio, 2014)
Having successfully helped readers develop a solid prayer life with the best-selling release of A Praying Life, author Paul Miller applies his expertise to tackle an even more important issue-love. After all, love is what holds all things together, it's what we're looking for, it's what we all need, and it's what we must learn how to give. But loving people is hard. Our neighbors, friends, kids, spouses, and even our enemies require a relentless, self-giving demonstration of love that only God can produce within us. Taking his cues from the perseverance and faithfulness portrayed in the book of Ruth, Miller sheds light on a biblical portrait of love that is sure to give us hope and transform our souls. Here is the help we need to embrace relationship, endure rejection, cultivate community, and reach out to even the most unlovable as we discover the power to live a loving life.